Hydrodynamic Performance of Euplectella Aspergillum: Simulating Real Life Conditions in the Abyss (Communications in Computational Physics, 2023)
We detail some of the understudied aspects of the flow inside and aroundthe Hexactinellid Sponge Euplectella aspergillum. By leveraging the flexibility of the Lattice Boltzmann Method, High Performance Computing simulations are performed todissect the complex conditions corresponding to the actual environment at the bottomof the ocean, at depths between 100 and 1,000 m. These large-scale simulations unveilpotential clues on the evolutionary adaptations of these deep-sea sponges in responseto the surrounding fluid flow, and they open the path to future investigations at theinterface between physics, engineering and biology.